2006
DOI: 10.3892/or.15.5.1321
|View full text |Cite
|
Sign up to set email alerts
|

Urinary gelatinase activities (matrix metalloproteinases 2 and 9) in human bladder tumors

Abstract: The ability to degrade type IV collagen, the major component of the basement membrane, is unique to gelatinases A and B. These two matrix metalloproteinases (MMPs) are most often linked to the malignant phenotype of tumor cells, and their expression is elevated in several cases of human tumor aggressiveness and overall survival. By gelatin zymography, we verified MMP activity in the urine of patients with bladder cancer. Of these patients, 10 had well-, 8 had moderately and 7 had poorly differentiated bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Zymography was performed using 7.5 % (w/v) polyacrylamide gels containing 0.1% (w/v) of gelatine as previously described (8,9). Briefly, serum samples or concentrated urine samples were mixed with sample buffer (10 mM Tris-HCl pH 6.8, 12.5% SDS, 5% sucrose, 0.1% bromophenol blue) and applied directely without prior heating or reduction to the gel.…”
Section: Patientsmentioning
confidence: 99%
“…Zymography was performed using 7.5 % (w/v) polyacrylamide gels containing 0.1% (w/v) of gelatine as previously described (8,9). Briefly, serum samples or concentrated urine samples were mixed with sample buffer (10 mM Tris-HCl pH 6.8, 12.5% SDS, 5% sucrose, 0.1% bromophenol blue) and applied directely without prior heating or reduction to the gel.…”
Section: Patientsmentioning
confidence: 99%
“…These zymographyc tests have some advantages over immunological assay such as lower cost, a more rapid time of execution and the possibility of simultaneously detecting multiple forms of the same enzyme. We have previously reported that urinary MMP-9 is increased in the high grade and advanced stage bladder cancers whereas only traces were detected in urine of healthy subjects (22), indicating that MMP-9 may be one of the important enzymes involved in the progression of neoplasias. Other researchers determined urinary MMPs lytic activity in urine from cancer patients (17) and they reported that MMP-9 was detected with higher frequency in the urine of patients with prostate cancer compared with those with bladder cancer.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…8-well chamber slides were used to culture IOMM-Lee cells at a concentration of 5x10 3 per well. After a 24-h incubation period, cells were transfected with pSV, pCB, pM and pMC.…”
Section: Construction Of Sirna Plasmid Vectors Targeting Cathepsin Bmentioning
confidence: 99%
“…In vitro cell proliferation ability was determined as viable cell mass in both untreated IOMM-Lee cells and cells transfected with pSV, pM, pCB and pMC using Cell Titer 96™ colorimetric assay. IOMM-Lee cells (5x10 3 ) were cultured in triplicate in 96-well plates and transfected with 1 μg of one of the shRNA expressing plasmid vectors following standard protocol. Untreated cells were also maintained under similar conditions to serve as the control (mock).…”
Section: Construction Of Sirna Plasmid Vectors Targeting Cathepsin Bmentioning
confidence: 99%
See 1 more Smart Citation